Clearing in financial networks with constrained equal awards - Shafransky, Ya. M. (Informatika (Minsk, Belarus), 2024)
Objectives. Financial networks with a rule of constrained equal awards for the distribution of the agent’s estate between its creditors are considered. The aim of the study is to develop an algorithm for constructing greatest clearing matrices for such networks under zero cash reserves of all agents. Methods. Graph theory and mathematical programming methods are used. Results. A polynomial-time algorithm for constructing the greatest clearing matrices for financial networks with a rule of constrained equal awards for the distribution of the agent's estate between its creditors is proposed. It is assumed that the cash reserves of each agent are equal to zero (funds received from other agents are distributed among creditors). The algorithm is based on the use of the identified properties of weighted strongly connected graphs. Necessary and sufficient conditions are obtained under which the greatest clearing matrix is different from zero at zero cash reserves of agents'. Conclusion. The developed approach can be used in constructing clearing algorithms for financial networks with other rules for distributing the agent’s estate between its creditors.